Diversity and potential invasiveness of insects in agricultural landscapes of Wonosobo, Central Java, Indonesia - SAKINA ENOVA RAHMADHANI; SIBRINA SALSABILA; ROI ANDRIANTO; SYARIFAH HASNA ROSYIDA; QUROTUL AINIA; ARU DEWANGGA; AHMAD DWI SETYAWAN (Asian Journal of Agriculture, 2025)
Abstract. Rahmadhani SE, Salsabila S, Andrianto R, Rosyida SH, Ainia Q, Dewangga A, Setyawan AD. 2025. Diversity and potential invasiveness of insects in agricultural landscapes of Wonosobo, Central Java, Indonesia. Asian J Agric 9: 663-670. Altitude and microclimatic variation act as key ecological filters that shape species diversity, community structure, and invasion potential altitude, microclimate, and land-use intensity jointly structure insect communities in the agricultural landscapes of Wonosobo, Central Java, Indonesia. Surveys across lowland Karangsambung (621 masl), mid-elevation Blederan (969 masl), and highland Sembungan (2,056 masl) recorded 57 species from 31 families, revealing clear diversity gradients. Species richness and functional balance peaked at mid-elevation, where moderate temperatures and heterogeneous vegetation supported diverse herbivores, predators, and pollinators. Lowland sites retained high diversity driven by warm conditions and productive cropping systems. In contrast, highland assemblages were simplified and dominated by synanthropic Diptera (Musca domestica, Leucostoma simplex), reflecting harsh climatic filters and nutrient-enriched soils. NMDS-envfit analyses highlighted altitude, temperature, illumination, and wind as the main determinants of community structure. Invasiveness remained low overall, but disturbance-tolerant taxa increased with elevation. These findings emphasize the importance of vegetation heterogeneity, microclimate buffering, and biological control in sustaining ecological stability. As climate warming accelerates, mid-elevation agroecosystems may become critical resilience zones for conserving biodiversity and maintaining agricultural sustainability.